Shark species identification from bite marks on a Short-finned Pilot Whale, Globicephala macrorhynchus (Ocean and Coastal Research, 2022)
A Short-finned Pilot Whale, Globicephala macrorhynchus, was found dead and with shark bites along its body on a beach in northeast Brazil. The present study aimed to identify the shark species responsible for the bites as well as to estimate its/their total length. Species identification was performed using the bite marks, which were of the same diameter, suggesting they were infected by one or more Tiger sharks of similar size. The characteristics of the bites and the shape and distribution of the marks left by the teeth pointed to the Tiger Shark, Galeocerdo cuvier. The total length of the Tiger Shark or sharks was estimated at between 257 and 288 cm, based on the perimeter contour of each bite and the interdental distance inferred from the marks on the whale. This suggests that the bites were inflicted by one or more sub-adult specimens.